Intradural spinal arachnoid cysts versus spinal arachnoid webs: a retrospective analysis of incidence, imaging findings and clinical presentation at a single institution - Stay, Rourke M.; Cromie, Blake S.; Rogers, Christopher D.; Pahl, Douglas W. (Frontiers in Musculoskeletal Disorders, 2025)
PurposeIntradural spinal arachnoid cysts (SACs) and spinal arachnoid webs (SAWs) are rare extramedullary lesions in the spine. We aimed to assess the relative incidence of the two entities while also better assessing the similarities and differences in imaging appearance and clinical presentation.MethodsA retrospective analysis was performed of the incidence, imaging features, and clinical presentation of SACs and SAWs at a single institution from 2015 to 2021.ResultsThere were 12 cases of SACs and 9 cases of SAWs. The incidence of cysts was .050% and the incidence of webs was .037%. The clinical presentation was similar in the two groups, with the most common signs and symptoms being back pain followed by leg pain. Other signs of myelopathy were common in both groups including absent or diminished reflexes, decreased sensation, and decreased strength. The locations of the cysts were: 1 cervical (8%), 6 thoracic (50%), 5 lumbar (42%). All of the cervical and thoracic cysts caused cord compression. All 9 webs caused focal cord compression (scalpel sign).ConclusionSACs and SAWs are both rare lesions that we believe have a similar incidence, with cysts being only a little more common in our cohort. As they both often present with signs and symptoms of myelopathy, imaging findings are more useful in distinguishing between the two entities. The location of the cyst and the appearance of mass effect on the cord are helpful, as webs cause a focal compression, the scalpel sign, while cysts cause broader and smoother compression.